Herramienta computacional para la selección de indicadores de eficiencia y rentabilidad en los proyectos potenciales de inyección continúa de vapor en Ecopetrol S.A. (2018)
As part of the set of activities to produce a computational tool that is the title of the project, this research document evaluated and analyzed the key KPIs of 18 fields worldwide considered successful, which have implemented the continuous injection of steam as a method of recovery improved. This analysis was carried out to compare the operational, geological and petrophysical parameters of two Colombian fields in which the continuous injection of steam is implemented as an improved recovery method in the middle Magdalena Valley basin. The objective of the research was to search for parameters that were measurable and traceable, which would allow both projects to be successful in terms of operational and economic efficiency.